The effect of the ryanodine receptor gene on the reproductive traits of Welsh sows - ZhukorskyiО. М.; TsereniukО. М.; VashchenkoP. А.; Khokhlov, A. M.; Chereuta, Y. V.; AkimovО. V.; Kryhina, N. V. (Regulatory Mechanisms in Biosystems, 2022)
The reproductive performance of sows largely determines the efficiency of the entire pig farming industry. The purpose of our work is the evaluation of polymorphism of the ryanodine receptor gene and its impact on the reproductive traits of sows of the Welsh breed of pigs. For this study, 148 pigs of the Welsh breed were used. The reproductive traits of sows were evaluated in two adjacent generations. We conducted a comprehensive assessment of the reproductive ability of sows using the SIRQS (selection index of reproductive qualities of sows), determined phenotypic consolidation coefficients and assessed the genetic potential of the animals’ productivity. The polymorphism of the RYR1 gene was determined using polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP). Data processing was performed using single-factor analysis of variance (ANOVA). Polymorphism of the ryanodine receptor gene in sows of the Welsh pig breed was evaluated. 8.0% of the animals were identified as carriers of the mutant allele of the RYR1 gene. However, no homozygous RYR1-nn animals were found. Pigs of the maternal generation carrying the homozygous NN genotype had better reproductive performance in all indicators. Sows that were carriers of the mutant allele were characterized by lower values of the genetic productivity potential compared with the entire estimated population for all productive traits. Sows which were free of the mutant allele of the RYR1 gene were characterized by large values of the SIRQS index. The values of the coefficients of phenotypic consolidation of the number of live born piglets in sows without the mutant allele were lower than in sows with the mutant allele n. Better performance of sows free of the mutant allele of the RYR1 gene was established over sows carrying it in all evaluated traits of reproductive capacity (for different traits P ranged from 0.021 to 1.0*10–4), except for number of piglets born alive per sow in the daughter generation. Sows with the NN genotype had better selection index values by 15.7% in the maternal generation and by 10.2% in the daughter generation. In order to increase the reproductive ability of sows in the studied population of Welsh pigs and achieve similar results in other herds of this breed, animals free from the mutant allele of the RYR1 gene should be selected for further reproduction in the process of breeding, while on the contrary, carriers of this gene should be gradually eliminated from the herd. To carry out breeding work, further research is needed on the entire population of Welsh pigs for the RYR1 gene.